Gravitational binary-lens events with prominent effects of lens orbital motion - Park, H.; Udalski, A.; Han, C.; Gould, A.; Beaulieu, J.; Tsapras, Y.; Szymanski, M.; Kubiak, M.; Soszynski, I.; Pietrzynski, G.; Poleski, R.; Ulaczyk, K.; et al. (Institute of Physics Publishing, 2013)
Gravitational microlensing events produced by lenses composed of binary masses are important because they provide a major channel for determining physical parameters of lenses. In this work, we analyze the light curves of two binary-lens events, OGLE-2006-BLG-277 and OGLE-2012-BLG-0031, for which the light curves exhibit strong deviations from standard models. From modeling considering various second-order effects, we find that thedeviations are mostly explained by the effect of the lens orbital motion. We also find that lens parallax effects can mimic orbital effects to some extent. This implies that modeling light curves of binary-lens events not considering orbital effects can result in lens parallaxes that are substantially different from actual values and thus wrong determinations of physical lens parameters. This demonstrates the importance of routine consideration of orbital effects in interpreting light curves of binary-lens events. It is found that the lens of OGLE-2006-BLG-277 is a binary composed of a low-mass star and a brown dwarf companion.